Winter carnival in a western town: identity, change, and the good of the community - Gabbert, Lisa, author; Utah State University Press, publisher (Colorado State University. Libraries, 2011)
Describes the origin of the winter carnival held in McCall, Idaho and tells what goes on there.
1. Relations of Self and Community: Participation and Conflict in Winter Carnival -- 2. Sculpting Relationships: Aesthetics, Citizenship, and Belonging in Winter Carnival Art -- 3. On Neon Necklaces and Mardi Gras Beads: Style and Audience in Winter Carnival Parades -- 4. Creating, Remaking, and Commemorating History in Games of Skill and Chance: Winter Carnival as Historical Process -- 5. Laughter, Ambivalence, and the Carnivalesque: Lake Monsters and Festive Culture -- Conclusion -- Appendix: Winter Carnival Events.
Keywords: Carnival -- Idaho -- McCall; Winter festivals -- Idaho -- McCall; Community life -- Idaho -- McCall; Social change -- Idaho -- McCall; McCall (Idaho) -- Social life and customs